Qualidade de vida das mulheres com sintomas irritativos da bexiga: Influência da eletroestimulação dos nervos Tibial Posterior e Parassacral - Bizarria, Larissa Bezerra (2020)
Introduction: bladder irritating symptoms are characterized through clinical investigation in women with overactive bladder (OB). Life`s Quality (LQ) becomes determined by urinary urgency, with or without Urinary Incontinence (UI), commonly accompanied by high urinary frequency during the day (polyuria) and at night (nocturia). Objective: analyze the QOL of women with OB undergoing Posterior Tibial Nerve Electrostimulation (EENTP) versus Parasacral Electrostimulation (EEPS). Methods: prospective study, randomized by convenience, with a descriptive and analytical approach of the LQ of 49 women. It was developed at the Urogynecology Clinic of Hospital Geral de Fortaleza (HGF), from May 2014 to May 2017. They were divided into two groups: 27 patients underwent EENTP (Group 1), and 22, EEPS (Group 2). The following values were submited statistical significance: p1 (EENTP analyzed “pre” and “post”), p2 (EEPS analyzed “pre” and “post”), p3 (EENTP versus EEPS analyzed “post”). Before the first service with EE and after the tenth service, the questionnaires were applied: semi-structured, referring to QoL in the UI (King's Health Questionnaire - KHQ's), the specific structured about BH (Overactive Bladder Questionnaire - OAB-V8), and the unstructured Voiding Diary (DM) for assessment of Daytime (FUD) and Nighttime (FUN) Urinary Frequencies. Statistical analysis was processed using the Statistical Package for the Social Sciences (SPSS) version 20.0, using Pearson's Chi-square test, likelihood ratio, Wilcoxon and Mann Whitney U test, considering p<0,05. Results: it was found that group 2 (EEPS) in the “pre” vs. “post” showed better therapeutic response (Wilcoxon test) (p<0.05), when compared to the EENTP (group 1), according to the KHQ's instruments in the domains General Health Perception (p2=0.009), Impact of UI (p2=0.017), Task Limitation (p2=0.003), Physical Limitation (p2=0.012), Sleep (p2=0.012), as the EENTP (Group 1) presented KHQ's significance only in the Emotion domain (p1=0.024) . Regarding the “post” therapeutic analysis in Groups 1 and 2 (Mann Whitney U test), only KHQ’s, in the Gravity Measures domain, was statistically significant (p3=0.032). Both groups obtained significance in the OAB-V8 in the “pre” vs. “Post” (Wilcoxon test) of the therapeutic forms with EENTP (p1<0.001) and EEPS (p2=0.001). The EENTP (p1=0.006) and EEPS groups (p2=0.012) also showed statistical significance in DM (Wilcoxon test) in relation to FUN. Conclusion: the electrostimulation of the posterior tibial and parasacral nerves showed a significant improvement of the clinical symptoms and consequently improvement of quality of life of female patients with bladder irritatin symptoms. The parasacral electroestimulation presented better results in the applied instruments, demonstrating better results in the quality of life.